Deletions linked to PROG1 gene participate in plant architecture domestication in Asian and African rice. Issue 1 (December 2018) - Wu, Yongzhen; Zhao, Shuangshuang; Li, Xianran; Zhang, Bosen; Jiang, Liyun; Tang, Yanyan; Zhao, Jie; Ma, Xin; Cai, Hongwei; Sun, Chuanqing; Tan, Lubin
Abstract Improving the yield by modifying plant architecture was a key step during crop domestication. Here, we show that a 110-kb deletion on the short arm of chromosome 7 in Asian cultivated rice (Oryza sativa ), which is closely linked to the previously identifiedPROSTRATE GROWTH 1 (PROG1 ) gene, harbors a tandem repeat of seven zinc-finger genes. Three of these genes regulate the plant architecture, suggesting that the deletion also promoted the critical transition from the prostrate growth and low yield of wild rice (O .rufipogon ) to the erect growth and high yield of Asian cultivated rice. We refer to this locus asRICE PLANT ARCHITECTURE DOMESTICATION (RPAD ). Further, a similar but independent 113-kb deletion is detected at theRPAD locus in African cultivated rice. These results indicate that the deletions, eliminating a tandem repeat of zinc-finger genes, may have been involved in the parallel domestication of plant architecture in Asian and African rice. Plant architecture transition is one of the great consequences during rice domestication. Here, the authors find that chromosomal deletions linked to the previously knownPROG1 gene also participate in plant architecture domestication in both Asian and African cultivated rice.